Dual Simplex Method for Optimal Coordination of DOCR’s in Distribution System with D-FACTS - A. Chaghi (International Journal of Information Science and Technology, 2019)
The problem of setting and coordination of Directional Over-Current Relay (DOCR) is a highly constrained optimization problem that has been solved as a linear programming problem. The calculation of the time dial setting (TDS) and pick up current (I P) setting of the relays is the core of the coordination. This paper calculates the TDS by choosing one of the available pick up current settings as the predetermined value, in this paper it will be set at 0.5, 1 and 1.5. The LP Dual simplex method is used to determine the optional TDS of the relays in compensated system by series FACTS devises ie Thyristor Controlled Series Capacitor (TCSC). A sample system of IEEE 33 bus distribution system is used to demonstrate the feasibility and efficiency of the developed method.